2006
DOI: 10.1002/app.24030
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization behavior of glass‐bead‐filled polypropylene

Abstract: The effects of the glass-bead content and size on the nonisothermal crystallization behavior of polypropylene (PP)/glass-bead blends were studied with differential scanning calorimetry. The degree of crystallinity decreased with the addition of glass bead, and the crystallization temperature of the blends was marginally higher than that of pure PP at various cooling rates. Furthermore, the half-time for crystallization decreased with an increase in the glassbead content or particle size, implying the nucleatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…It is likely that the dispersed clay particles hinder the formation of large crystalline domains in the restricted and confined space. Interestingly, this behavior is similar to our observations in PP/glass bead blends 48. In Figure 5, the relationship between the relative degree of crystallinity and the temperature for the PE/clay nanocomposites at various cooling rate is presented.…”
Section: Resultssupporting
confidence: 86%
“…It is likely that the dispersed clay particles hinder the formation of large crystalline domains in the restricted and confined space. Interestingly, this behavior is similar to our observations in PP/glass bead blends 48. In Figure 5, the relationship between the relative degree of crystallinity and the temperature for the PE/clay nanocomposites at various cooling rate is presented.…”
Section: Resultssupporting
confidence: 86%
“…The fibers acted as heterogeneous nucleating agents to facilitate crystallization, and the t 1/2 of composite was shortened under the effect of fibers. In addition, Misra and coworkers50 found that the t 1/2 was not only related to the addition of inorganic fillers, but also the contents and particle sizes of fillers.…”
Section: Resultsmentioning
confidence: 99%
“…Their geometry allows good dispersion and a close packing, resulting in an improved dimensional stability for different thermoplastics [13,28,29]. So far, many studies have been devoted to PP filled with the conventionally used inorganic soda lime glass, also known as A-glass [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Other glass types, such as the borosilicate glass (E-glass), have established themselves as the filling material of choice for glass-fiber reinforced composites [50], also in connection with PP [51][52][53].…”
Section: Introductionmentioning
confidence: 99%